Mariella Mehr's steinzeit: Narrating Trauma through Autofiction. - Gardner, Natasza (Feminist German Studies)
In her novel steinzeit (1981; stone age), Mariella Mehr exposes the cruelty that children of Yenish families in Switzerland experienced between 1926 and 1973 at the hands of Pro Juventute's Hilfswerk für Kinder der Landstraße, a charitable foundation purportedly dedicated to supporting the rights of children and youth. In the novel's protagonist, Mehr incorporates split identities, episodes of cyclical trauma, and alter egos to grapple with gendered and racialized experiences of trauma. I read steinzeit, a novel loosely inspired by Mehr's own experiences, as a work of autofiction, a genre within the broader category of life writing. Women writers have, for decades, turned to personal narratives and trauma literature as means to reconstruct selfhood. Reconstructing an autonomous selfhood through narrative ultimately proves impossible for Mehr's Yenish protagonist, however, given that the protagonist exists within a state system that continued marginalizing members of the Yenish community and failed to acknowledge Hilfswerk's damaging practices until 1986.